Applied statistics in business and economics - Doane, David P. (McGraw-Hill Irwin, 2009)
Offers an introduction to statistics concepts and applications in business and economics. This text and student CD provide an integration of technology in order to focus on the important practical concepts and applications as opposed to mechanics.